(untitled) (Altruistik : Jurnal Konseling dan Psikologi Pendidikan, 2021)
This research was conducted at SMPN 5 Bima City with the aim of knowing the relationship between authoritarian parenting and aggressive behavior of students at SMPN 5 Bima City. The population of this study was 230 subjects with a total sample of 37 subjects selected using the Simple Random Sampling technique. Collecting data using a questionnaire based on the Likert scale and tested using the Product Moment Correlation technique. The results of the analysis obtained a mean score of 86.38 which is classified in the high category and the score of the aggressive behavior variable is 84.00 which is classified in the high category. From the product moment correlation analysis, the correlation coefficient is r = 0.631 and a significant value is = 0.000 (Ï <0.05). This means that the hypothesis which reads that there is a relationship between authoritarian parenting and aggressive behavior in students at SMPN 5 Bima City in this study is accepted.